Устойчивость комплексов меди (ІІ) с денатурированной ДНК в растворах с разной ионной силой - Бабий, А.П.; Багавеев, И.А.; Уминский, А.А.; Саенко, Г.Н. (Биополимеры и клетка, 1986)
В широком интервале концентраций хлористого натрия и хлористой меди (II) исследовано взаимодействие в системе Сu(II)–денатурированная ДНК (дДНК). Рассчитаны «истинная» и кажущиеся константы устойчивости комплекса Сu(II) – ДНК. Экспериментально подтверждена хелатная природа спектроскопически регистрируемого комплекса Сu(II) – дДНК. У широкому інтервалі концентрацій хлористого натрію і хлористої міді (II) досліджено взаємодію у системі Сu (II)–денатурована ДНК (дДНК). Розраховано «справжню» і уявні константи стійкості комплексу Сu (II)–ДНК. Експериментально підтверджено хелатну природу комплексу Сu (II)–дДНК, який спектроскопічно реєструється. Conditions necessary for the formation and stability of Cu(II) complexes with the denatured DNA (dDNA) in solutions of various ionic strength are studied by the electron spectroscopy method. A chelate nature of the spectroscopically registered Cu(II) — dDNA complex in which Cu(II) ions form a bond with nitrogen base and phosphate group of biopolymer is experimentally confirmed. The «true» and seeming stability constants of the formed complexes are calculated. The possible structure of Cu(II) — dDNA complexes is suggested.